2016
DOI: 10.1136/neurintsurg-2016-012629
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of microsurgical clipping, endovascular coiling, and stent assisted coiling for unruptured anterior communicating artery aneurysms: a systematic analysis of observational studies

Abstract: While there are limitations to the data, EC resulted in a more favorable clinical outcome, and MC resulted in more robust aneurysm repair, for unruptured ACoA aneurysms. SAC had a higher treatment morbidity risk than EC, without reduction in retreatment rate. All treatments were effective in preventing SAH. The current pooled analysis of treatment outcomes provides a useful aid to pretreatment clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…While microsurgical clipping of ACoA aneurysms holds an advantage over endovascular coiling in terms of durability, it remains to be seen whether clipping holds a similar advantage over flow diversion. The meta-analysis of unruptured ACoA aneurysms showed angiographic recurrence and retreatment of 0% associated with clipping compared with 7.2% and 4.9%, respectively, associated with coiling 23. In the present study, complete occlusion was seen in 85% of aneurysms at an average last follow-up of 10.4 months post-treatment.…”
Section: Discussionsupporting
confidence: 42%
“…While microsurgical clipping of ACoA aneurysms holds an advantage over endovascular coiling in terms of durability, it remains to be seen whether clipping holds a similar advantage over flow diversion. The meta-analysis of unruptured ACoA aneurysms showed angiographic recurrence and retreatment of 0% associated with clipping compared with 7.2% and 4.9%, respectively, associated with coiling 23. In the present study, complete occlusion was seen in 85% of aneurysms at an average last follow-up of 10.4 months post-treatment.…”
Section: Discussionsupporting
confidence: 42%
“…Coiling with stent placement for patients with ruptured aneurysms on middle cerebral artery bifurcation or anterior communicating artery was avoided as much as possible after the previous study showed that aneurysms in these two locations were more likely to have a higher incidence of complications. 20 Several studies also showed that stent-assisted coiling of anterior communicating artery aneurysms 7,13 and middle cerebral artery aneurysms 10 had a higher complication rate than coiling alone. Therefore coiling with stent placement should be more strictly considered and used in the ruptured aneurysms on these two locations.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebrovascular diseases causing such controversy in regard to treatment are few in number [73]. The reasoning behind this continuous debate is that the prophylactic management of UIAs must be justified by a suitable procedurerelated outcome when compared to the anticipated natural history [74]. Despite clipping once being the management centerpiece, the swift refinement of endovascular procedures and innovation of flow diversion devices have steadily replaced surgery as the first line of therapy for UIAs.…”
Section: Clipping Of Solitary Unruptured Aneurysmsmentioning
confidence: 99%
“…Aneurysms of the anterior communicating artery are the most frequently reported in a large number of studies, possessing a higher risk of rupture than other locations while also being amenable to both endovascular and microsurgical techniques [36,74,[86][87][88][89]. The term may actually be overly broad, also including aneurysms of the A1 and A2 junctions of the anterior cerebral artery or belonging entirely to these two segments, but being indistinguishable from true ACoA aneurysms on angiographic studies [88].…”
Section: Clipping Of Solitary Unruptured Aneurysmsmentioning
confidence: 99%